THE ROLE OF GDP PER CAPITA, ECONOMIC FREEDOM INDEX AND POPULATION GROWTH TO POLITICAL STABILITY IN SOUTHEAST ASIAN COUNTRIES: IS THERE BEST CHOICES SUPPORTING THE WORLD IN PEACE? - Firmansyah, Muhamad Ferdy; Rusliana, Nanang; Maulana, Haikal Zulian; Nuraini, Sri Rahmi; Ridho, Muhamad (The Sunan Ampel Review of Political and Social Sciences, 2023)
This study aims to examine the role of economic growth, the index of economic freedom, and the population on political stability. Political stability is one of the factors that can determine the direction of development and economic growth towards the creation of prosperity. Politically stable countries can carry out better economic development. This research contributes to look at the factors that can support political stability in Southeast Asian countries. This study uses secondary data originating from the World Governance Indicator, World Bank Development Indicator and Heritage Foundation in the 2011-2020 period. This study was conducted in Southeast Asian countries, namely Indonesia, Malaysia, Thailand, Philippines, Singapore and Vietnam. The research method used is panel data regression. The results show that GDP Per capita and economic freedom index is a significant effect to political stability. On the other side, population growth has not significant impact to political stability. This proves that every country that has good political stability is supported by stable guaranteed economic freedom, and a controlled GDP per capita.